INDUCTIVE REASONING AS AN EFFECTIVE WAY TO ENHANCE WRITING PROFICIENCY: INDUCTIVE REASONING AS AN EFFECTIVE WAY TO ENHANCE WRITING PROFICIENCY - Koshkinbaeva, Zukhra (Журнал иностранных языков и лингвистики, 2025)
In contemporary education, writing proficiency is a cornerstone skill essential for academic success and effective communication. However, many students encounter difficulties in conveying their thoughts clearly and constructing coherent arguments. Inductive reasoning—a cognitive approach that enables individuals to derive general principles from specific observations—emerges as a powerful tool for enhancing writing proficiency. Inductive reasoning involves making generalizations based on specific observations or evidence. For instance, a student may observe that "students who attend writing workshops tend to submit higher-quality papers" and conclude that "participation in writing workshops improves writing quality." This reasoning process encourages students to gather evidence, identify patterns, and formulate general conclusions that can inform their writing.